2012
DOI: 10.5812/traumamon.4230
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Iranian Medical Interns Regarding Cardio-Pulmonary Resuscitation

Abstract: Objectives:Cardio-Pulmonary Resuscitation (CPR) is one of the most important procedures in emergency medicine. As new trends are evolving in medical education , we planned to evaluate the interests and knowledge of medical students regarding educational methods in CPR learning.Materials and Methods:In a cross-sectional analytical descriptive study, a standardized questionnaire was distributed among 180 medical interns at the Mashhad University of Medical Sciences. The questionnaire had three parts: demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 5 publications
2
9
1
Order By: Relevance
“…There was no difference between males and females regarding knowledge on CPR (table 3). Similar findings were seen in a study conducted by Ralapanawa DM et al 21 Another study done by Ravari H et al 22 among medical interns showed that males were more educated (p=0.041) than females. On the contrary, proper CPR information was higher among females(87%) than males (61%) in a study done among school students in Riyadh by Alanazi et al 23 .…”
Section: Discussionsupporting
confidence: 78%
“…There was no difference between males and females regarding knowledge on CPR (table 3). Similar findings were seen in a study conducted by Ralapanawa DM et al 21 Another study done by Ravari H et al 22 among medical interns showed that males were more educated (p=0.041) than females. On the contrary, proper CPR information was higher among females(87%) than males (61%) in a study done among school students in Riyadh by Alanazi et al 23 .…”
Section: Discussionsupporting
confidence: 78%
“…Immediate and efficient CPR based on enough knowledge and practical skills is essential to improve this situation (Filho et al,2006) as the quality of this intervention is influential for improving patient survival (Ravari et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in Iran and People’s Republic of China showed that only a small number of medical students were confident in their ability to carry out CPR and felt that they can do it correctly 22,23. Likewise, in a study carried out in Norway, it was found that most of the nursing student teams did not perform defibrillation accurately during CPR 24…”
Section: Introductionmentioning
confidence: 99%